ASSESSMENT OF OPERATION SAFETY OF THE RSG-GAS REACTOR TO SERVE RADIOISOTOPE TARGET IRRADIATION - Iman Kuntoro; Lily Suparlina; Purwadi Purwadi (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2022)
The RSG-GAS multipurpose reactor is operated to serve the utilization in the field of radioisotope production and NAA, material research. The reactor actually has power of 30 MW thermal, but upon considerations of efficiency and of most users requirements, the reactor is mostly operated at the power of 15 MW thermal, 5 days a week to produce a primary radioisotope from target of 2 grams U-235. To guarantee the safe operation and optimum utilization, a safety procedure was established. The paper is intended to assesst the operation safety in serving radioisotope target irradiation at its cycle operation. Assessment was carried out for core numbers 102 â€“ 105. The result shows that excess reactivity and shutdown margin reactivity are safe to provide the target irradiation in the core for each cycle operation.Â